Anthelmintic Potential of Agelasine Alkaloids from the Australian Marine Sponge Agelas axifera - Kanchana Wijesekera; Aya C. Taki; Joseph J. Byrne; Darren C. Holland; Ian D. Jenkins; Merrick G. Ekins; Anthony R. Carroll; Robin B. Gasser; Rohan A. Davis (Marine Drugs)
A recent high-throughput screening of the NatureBank marine extract library (7616 samples) identified an extract from the Australian marine sponge Agelas axifera with in vitro activity against an economically important parasitic nematode, Haemonchus contortus (barber’s pole worm). The bioassay-guided fractionation of the CH2Cl2/MeOH extract from A. axifera led to the purification of a new diterpene alkaloid, agelasine Z (1), together with two known compounds agelasine B (2) and oxoagelasine B (3). Brominated compounds (–)-mukanadin C (4) and 4-bromopyrrole-2-carboxylic acid (5) were also isolated from neighbouring UV-active fractions. All compounds, together with agelasine D (6) from NatureBank’s pure compound library, were tested for in vitro anthelmintic activity against exsheathed third-stage (xL3s) and fourth-stage larvae (L4s) of H. contortus and young adult Caenorhabditis elegans. Compounds 1, 2 and 6 induced an abnormal “skinny” phenotype, while compounds 2 and 6 also reduced the motility of H. contortus L4s by 50.5% and 51.8% at 100 µM, respectively. The minimal activity of agelasines against C. elegans young adults suggests a possible species-specific mechanism warranting further investigation. For the first time, the unexpected lability of agelasine H-8′ was explored using kinetic studies, revealing rapid deuterium exchange in MeOH-d4 at room temperature.